2018
DOI: 10.28982/josam.409968
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insulin resistance on House-Brackmann grade of facial paralysis in patients with Bell’s palsy

Abstract: How to cite / Atıf için: Özer G. The effect of insulin resistance on the House-Brackmann grade of facial paralysis in patients with Bell's palsy.This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives License 4.0 (CC BY-NC-ND 4.0) where it is permissible to download, share, remix, transform, and buildup the work provided it is properly cited. The work cannot be used commercially without permission from the journal. AbstractAim: Bell's palsy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Özer et al, in a similar way to our study, found a higher incidence of hyperglycemia and IR positivity and increased insulin values in most of their BP patients compared to the general population. 31 On the contrary, Bosco et al reported that IR could not provide helpful information about BP when compared to the oral glucose tolerance test (OGTT) and also noted that IR led to an increased risk of BP in obese patients. 9 In the same study, a significant relationship was found between BP and glucose metabolism dysfunction after 2-hour OGTT in patients with normal fasting glycemia compared to the control group and the authors suggested that IR could be a risk factor for neuropathic damage due to BMI.…”
Section: Parametersmentioning
confidence: 99%
“…Özer et al, in a similar way to our study, found a higher incidence of hyperglycemia and IR positivity and increased insulin values in most of their BP patients compared to the general population. 31 On the contrary, Bosco et al reported that IR could not provide helpful information about BP when compared to the oral glucose tolerance test (OGTT) and also noted that IR led to an increased risk of BP in obese patients. 9 In the same study, a significant relationship was found between BP and glucose metabolism dysfunction after 2-hour OGTT in patients with normal fasting glycemia compared to the control group and the authors suggested that IR could be a risk factor for neuropathic damage due to BMI.…”
Section: Parametersmentioning
confidence: 99%